SYNTHETIC FOOD COLORS - ARE THEY SAFE? - Kulkarni, Jyoti (International Journal of Research -GRANTHAALAYAH, 2014)
Colors in foods are always tempting whether they are natural or synthetic. Synthetic colors are commonly used in foods & beverages as they are easily available, economic and intense whereas natural food colors are costly, availability is limited and range of color is also limited but whether synthetic colors are safe enough as far as health is concerned is a serious matter and to work over it is a matter of interest. To fulfil the ultimate goal of reducing the total exposure to colors, data on dietary intake of food colors needs to be generated urgently in the country.